2001
DOI: 10.1105/tpc.13.3.535
|View full text |Cite
|
Sign up to set email alerts
|

A Small Decrease of Plastid Transketolase Activity in Antisense Tobacco Transformants Has Dramatic Effects on Photosynthesis and Phenylpropanoid Metabolism

Abstract: Transketolase (TK) catalyzes reactions in the Calvin cycle and the oxidative pentose phosphate pathway (OPPP) and produces erythrose-4-phosphate, which is a precursor for the shikimate pathway leading to phenylpropanoid metabolism. To investigate the consequences of decreased TK expression for primary and secondary metabolism, we transformed tobacco with a construct containing an antisense TK sequence. The results were as follows: (1) a 20 to 40% reduction of TK activity inhibited ribulose-1,5-bisphosphate reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
156
4
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(169 citation statements)
references
References 59 publications
8
156
4
1
Order By: Relevance
“…Analysis of tobacco plants expressing an antisense construct for plastid TK demonstrated that a small reduction in the activity of this enzyme by 20 to 40% inhibited photosynthesis and significantly decreased the levels of aromatic amino acids and phenylpropanoids (Henkes et al, 2001). Comparison of these results with those from analysis of antisense SBPase and FBPaldolase plants showed that these changes are unique to TK and do not simply reflect a general reduction in the availability of carbon from the C3 cycle (Haake et al, 1998(Haake et al, , 1999Harrison et al, 1998).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Analysis of tobacco plants expressing an antisense construct for plastid TK demonstrated that a small reduction in the activity of this enzyme by 20 to 40% inhibited photosynthesis and significantly decreased the levels of aromatic amino acids and phenylpropanoids (Henkes et al, 2001). Comparison of these results with those from analysis of antisense SBPase and FBPaldolase plants showed that these changes are unique to TK and do not simply reflect a general reduction in the availability of carbon from the C3 cycle (Haake et al, 1998(Haake et al, , 1999Harrison et al, 1998).…”
Section: Introductionmentioning
confidence: 92%
“…Plastid transketolase (TK) is another enzyme in the C3 cycle that has been shown to have a significant effect on photosynthesis and growth in antisense tobacco plants (Henkes et al, 2001). Analysis of tobacco plants expressing an antisense construct for plastid TK demonstrated that a small reduction in the activity of this enzyme by 20 to 40% inhibited photosynthesis and significantly decreased the levels of aromatic amino acids and phenylpropanoids (Henkes et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Published results suggest a more general role for xanthophyll cycle: it was shown that downregulation of nitrate reductase activity, and thus lower NADPH use, increases zeaxanthin levels (Foyer et al, 1994). Consistently, inhibition of transketolase activity increases starch accumulation and zeaxanthin levels in dark adapted leaves, allowing for faster and stronger excess energy dissipation in the event of excess light (Henkes et al, 2001). This suggests that zeaxanthin accumulation is a tool for preventive modulation of the amplitude and rate of heat dissipation response in relation to the cell metabolism and redox poise with higher NADPH/NADP þ ratios being an indication of stronger sensitivity to excess light.…”
Section: What Is the Physiological Role Of Ph-independent Quenching Imentioning
confidence: 89%
“…0.5 and 0.9 (e.g. Labate et al 1990;Henkes et al, 2001). However, sensitivity tests show that emission results are hardly sensitive to this ratio (results not presented).…”
Section: Emission Modelsmentioning
confidence: 99%